Studies of hadronic event structure and comparisons with QCD models at the Zº resonance - Dova, María Teresa (1992)
The structure of hadronic events from Z0 decay is studied by measuring event shape variables, factorial moments, and the energy flow distribution. The distributions, after correction for detector effects and initial and final state radiation, are compared with the predictions of different QCD Monte Carlo programs with optimized parameter values. These Monte Carlo programs use either the second order matrix element or the parton shower evolution for the perturbative QCD calculations and use the string, the cluster, or the independent fragmentation model for hadronization. Both parton shower and O(α2s) matrix element based models with string fragmentation describe the data well. The predictions of the model based on parton shower and cluster fragmentation are also in good agreement with the data. The model with independent fragmentation gives a poor description of the energy flow distribution. The predicted energy evolutions for the mean values of thrust, sphericity, aplanarity, and charge multiplicity are compared with the data measured at different center-of-mass energies. The parton shower based models with string or cluster fragmentation are found to describe the energy dependences well while the model based on the O(α2s) calculation fails to reproduce the energy dependences of these mean values.